Probiotics formulated from indigenous bacteria from goat digestive tract and fed with fermented mixed feed Eichhornia crassipes and Zea mays cobs (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Isnawati, Muhaimin FI, Rahayu DA, Fitrihidajati H, Ratnasari E. 2023. Probiotics formulated from indigenous bacteria from goat digestive tract and fed with fermented mixed feed Eichhornia crassipes and Zea mays cobs. Biodiversitas 24: 2906-2911. The provision of cellulolytic bacteria as probiotics in goat feed is crucial to their growth and health. Therefore, this study aimed to monitor the effects of providing cellulolytic bacteria isolated from the digestive tract of goats as probiotics in feed rations. Probiotic cellulolytic bacteria were isolated from the digestive tract of goat food fed with a fermented feed containing a combination of hyacinth and corn cob. In this study, the probiotic types are also different from other studies, namely Bacillus pumilus, Bacillus brevis, and Pseudomonas diminuta. Therefore, its effects on the vegetative and generative growth from various age groups and sexes of test goats are investigated. The goats tested were divided into two groups: fed with and without probiotics, with subgroups based on their sexes (male and female) and age groups (baby, juvenile, and adult). The tested goats were fed for 35 days, and their weight gain and sperm quality were observed; in general, weight gain was observed in goats fed the probiotics. Furthermore, the quality of spermatozoa in adult male goats fed with probiotics is higher than without probiotics, which includes its viability (52.2% to 36.9%), motility (48.1% and ++++ to 33.2% and ++), volume and concentration (1.05 mL/ejaculate with 3.7×109 cells/mL to 0.55 mL/ejaculated with 2.6×109 cells/mL). Based on the results, adding cellulolytic bacterial probiotics to the feed promotes the vegetative growth of goats in different age groups, in male and female goats. Also, it improves reproductive performance in adult male test goats.
Keywords: Cellulolytic bacteria, corn cob, feed, synbiotics, water hyacinth